A photoaffinity labeling strategy identified EF1A1 as a binding protein of cyclic dinucleotide 2′3′-cGAMP. Issue 1 (20th January 2022) - Hou, Yingjie; Lu, Heng; Li, Jinxin; Guan, Zhenyu; Zhang, Jianan; Zhang, Wentao; Yin, Changsong; Sun, Le; Zhang, Yaoyang; Jiang, Hong
Summary: 2′3′-cyclic GMP-AMP (2′3′-cGAMP), generated by cyclic GMP-AMP synthase (cGAS) under activation by cytosolic DNA, has a vital role in innate immune response via its receptor protein stimulator of interferon genes (STING) to fight viral infections and tumors. In order to have a complete understanding of biological functions of 2′3′-cGAMP, it is important to find out whether 2′3′-cGAMP has other unrevealed binding proteins present in mammalian cells and executes unknown functions. Here we report the 2′3′-cGAMP-based photoaffinity probes that capture and isolate 2′3′-cGAMP-binding proteins. These probes enable the identification of some potential 2′3′-cGAMP-binding proteins from HeLa cells. EF1A1, an essential protein regulating protein synthesis, is further validated to associate with 2′3′-cGAMP in vitro and in cells to impede protein synthesis. Thus, our studies provide a powerful approach to enable identification of the 2′3′-cGAMP interactome, discover unknown functions of 2′3′-cGAMP, and understand its physiological/pathological roles in tumor immunity and immune-related diseases. Graphical abstract: Highlights: Photoaffinity probes of 2′3′-cGAMP enable identification of its interactome 2′3′-cGAMP associates with EF1A1 in EF1 complex in preference to free-form EF1A1 2′3′-cGAMP prevents GTP binding to EF1A1 in EF1 complex 2′3′-cGAMP impedes protein synthesis independently from STING Abstract : Hou et al. develop the photoaffinity probes of 2′3′-cGAMP to identify its interactome, and discover its STING-independent function to inhibit protein synthesis by association with EF1A1 in EF1 complex. Their studies provide a useful approach to understand biological functions of 2′3′-cGAMP and its roles in immune-related diseases.